Colombian labyrinth : the synergy of drugs and insurgency and its implications for regional stability - Rabasa, Angel (RAND, 2001)
U.S. policy toward Colombia has been driven to a large extent by counter-narcotics considerations, but the evolving situation in that South American country confronts the United States with as much of a national security as a drug policy problem. Colombia is a geostrategically important country, whose trajectory will influence broader trends in the Andean region and beyond. Colombian Labyrinth examines the sources of instability in the country; the objectives, strategy, strengths, and weaknesses of the government, guerrillas, and paramilitaries and the balances among them; and the effects of the current U.S. assistance program. Possible scenarios and futures for Colombia are laid out, with implications for both the United States and neighboring countries. The authors find that instability in Colombia stems from the interaction and synergies of the underground drug economy and armed challenges to the state's authority. Solutions to the core problem--the weakness of the Colombian state--must focus on resolving the broader set of political-military challenges that result from the convergence of drug trafficking and insurgency. The authors recommend that Colombia's military and institutional capabilities be improved to enable the Colombian government to regain control of the countryside and that, at the same time, the United States work with Colombia's neighbors to contain the risk of spillover and regional destabilization.